Effect of beam-column joints flexibility on the seismic response of setback RC buildings designed according to the Algerian seismic code (Fracture and Structural Integrity, 2022)
The Algerian seismic code assumes that the beam-column joints in monolithic reinforced concrete (RC) buildings are fully rigid. However, many experiments have proven the existence of relative rotations in these connections, and then the presence of relative transfer of bending moment. The present work aims to investigate the effect of beam-column joints modelling on the global seismic behaviour of reinforced concrete (RC) moment-resisting frames buildings, designed according to the Algerian seismic code recommendations. To consider the nonlinear deformation of the connections, an analytical model developed recently is used. This model includes two important deformation mechanisms; the first one covers the slippage of the continuous reinforcement within the column, whereas the second involves slippage caused by creating bending cracks at the extremities of the beams. Three multi-storey RC frames with different setback geometry, including a reference frame, are studied considering the connections as rigid/deformable. The nonlinear static procedure or pushover analysis is used to perform a nonlinear analysis of the studied structures and the results in terms of capacity curve, target displacement, storey drift, storey stiffness and the response reduction factor are presented. The results show the necessity of considering the beam-column connection flexibility when modelling this type of building.
Keywords: Beam-column joints; pushover analysis; RC buildings; setback buildings; seismic behaviour